RECONTEXTUALIZATION IN THE TRANSLATION OF PORTUGUESE CHILDREN’S BOOKS INTO CHINESE - Zhang, Jingwen (2021)
In the second decade of this century, children's picture storybooks became popular in China and Portuguese works entered the Chinese market in force, making the translation indispensable and sought after. The present work, based on the Chinese version of about thirty Portuguese children's picture storybooks published in China, aimed at the Chinese young audience, studies, analyzes and comments on the translation procedures used, in the context of recontextualization, aiming to make a small contribution to the prosperity of the translation of Portuguese children's literature to Chinese, in the service of intercultural communication between the Chinese world and the Portuguese world.